2012
DOI: 10.1097/mcg.0b013e3182557307
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Management of HER2-positive Advanced Gastric and Gastroesophageal Junction Cancer

Abstract: In the past, patients with advanced or metastatic gastric or gastroesophageal junction cancer have had few treatment options and generally poor survival rates. The human epidermal growth factor receptor 2 (HER2) has been identified as a potential therapeutic target because of its overexpression or gene amplification in 6% to 35% of gastric or gastroesophageal junction cancers, although the methods of assessment and prognostic value of HER2 have been subject to debate. The phase III Trastuzumab for Gastric Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…ERBB2 is a member of the epidermal growth factor receptor family, which has previously been associated with the enhanced proliferation rates of tumor cells (38). In addition, previous studies have demonstrated that ERBB2 is a target gene of miR-375 (20), that the PI3K/Akt signal pathway is associated with ERBB2 regulation, and that the activation of the ERBB2/PI3K/Akt pathway may promote resistance of cancer cells to drugs (26).…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2 is a member of the epidermal growth factor receptor family, which has previously been associated with the enhanced proliferation rates of tumor cells (38). In addition, previous studies have demonstrated that ERBB2 is a target gene of miR-375 (20), that the PI3K/Akt signal pathway is associated with ERBB2 regulation, and that the activation of the ERBB2/PI3K/Akt pathway may promote resistance of cancer cells to drugs (26).…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79] It is expressed in normal epithelial cells, and amplification and/or overexpression of this gene has been reported in up to 30% of breast cancers 80 and in 9% to 27% of patients with gastric cancer. Overexpression of HER2/neu is slightly greater at the esophagogastric junction in comparison to the stomach 81,82 and overexpression in the stomach varies with histologic type (intestinal-type greater than diffuse type) and differentiation (moderately differentiated greater than poorly differentiated). 83 ERBB2 (HER2/neu) appears to be an important prognostic factor in gastric cancer, but the literature is conflicting, as not all studies have shown an association between HER2/neu overexpression and poor prognosis.…”
Section: Mek Genementioning
confidence: 99%
“…In ToGA trial, a combination of chemotherapy and trastuzumab demonstrated a significant OS benefit in metastatic gastric cancer patients. [15] Its value as a prognostic factor of HER2 in gastric cancer is controversial and may vary based on whether the patient receives chemotherapy. For instance, Terashima et al [16] investigated the HER2 status in gastric cancer and found that HER2 was not a prognostic marker in the ing HER2 with antibody caused significant changes in the radiosensitivity of tumor cells.…”
Section: Discussionmentioning
confidence: 99%